DNA-relaxing enzyme from Micrococcus luteus. - Hecht, R (1977)
A DNA-relaxing enzyme which catalyzes the conversion of superhelical DNA to a non-superhelical covalently closed form has been purified from Micrococcus luteus to near homogeneity by two chromatographic steps. The enzyme is a single polypeptide chain. As determined by sodium dodecyl sulfate - polyacrylamide gel electrophoresis and gel filtration on Sephadex G 150, the molecular weight is 115,000. The DNA-relaxing activity determined as a function of enzyme concentration follows a sigmoidal curve. The enzyme requires Mg++ for activity. In the presence of 4.5 mM Mg++ addition of 50-250 mM KCl yields incompletely relaxed DNA molecules (intermediates); intermediates are also observed in the absence of KCl, when the reaction is carried out at 0 degree C or at Mg++ concentrations exceeding 10 mM.